Enhancing the Entrepreneurial Intention on the Regulatory Impact Assessment: Evidence from Wholesalers Experiences - Zulhamri Abdullah; Wan Fauziah Wan Yusoff; Fakhrul Anwar Zainol (International Journal of Supply Chain Management, 2020)
The purpose of this paper is to investigate the current status of RIA within the agriculture industry in Malaysia. This paper also identifies the mechanism used such as structure remedies in assisting economy to enhance agriculture industry in Malaysia. The study employs questionnaireâ€survey approach to obtain the perceptions of wholesalers from the central, south, and east coast of Malaysia. The instruments developed have been validated using tests for reliability and validity. Specifically, a cost benefit analysis has been applied based on the eight options of regulatory impact assessment. This finding found that majority of the respondents are inheriting the business from their family and being monopolized by Chinese wholesalers. Most of them do not have any contract with agriculture producers and the price of agriculture products was decided by producers or farmers itself. Most of them seem not be well known about grading, packaging and labeling (GPL) rules and they do not need this rule due to proliferation of cost production. Undeniably, the implementation of regulatory analysis can maximize the satisfaction for both; wholesalers and producers. Therefore, the government should provide more incentives in order to encourage an attitude to implement this new regulation. The study adds solid empirical evidence to the evolving agri-entrepreneurship literature on the impacts of agriculture regulations. Specifically, this study also contributes the dearth of evidence on the efficacy of the introduction of regulatory impact analysis in a developing country.